Investigation and theoretical modeling of the nonlinear optical properties of 5,10-A₂B₂ porphyrins - Zawadzka, Monika (Trinity College (Dublin, Ireland). School of Chemistry, 2012)
An optical limiter is a device which is transparent to ambient light but becomes opaque upon high intensity laser irradiation. Such irradiation is dangerous to human eyes and light sensitive detectors. Porphyrins, which are a group of conjugated macrocyclic dyes, are interesting candidates for optical limiting (OL) applications. This is because they exhibit strong positive nonlinear absorption (NLA) in the spectral window between Soret and Q- bands in the visible range. The NLA arises due to the sequential absorption of photons and is referred to as reverse saturable absorption (RSA). RSA occurs when the excited states absorb light more efficiently than the ground state, which is phenomenally expressed as transmission drop with intensity. Although much is known about the linear and nonlinear optical properties of porphyrins, it is still not fully understood how the structural features of these macrocycles impact their OL performance.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin